Aide and Client Safety "Should Go Hand-In-Hand": Qualitative Findings From Home Care Aides, Clients, and Agency Leaders. (April 2023) - Brouillette, Natalie M.; Markkanen, Pia K.; Quinn, Margaret M.; Galligan, Catherine J.; Sama, Susan R.; Lindberg, John E.; Karlsson, Nicole D.
Retention of the home care (HC) aide workforce is essential to meet the needs of our aging population. Some studies suggest that improving HC safety could increase job retention. This study objective was to explore qualitatively the connection between aide and client safety and factors impacting this care relationship. Data consisted of audio-recorded, verbatim responses to open-ended questions of two focus groups with aides ( n = 10), two in-person interviews with HC agency managers, and 37 phone interviews with those working in (aides, n = 16; managers, n = 12) and receiving (clients, n = 9) HC. Clients reported home layout and accessibility as safety concerns. Aides and managers reported that client family members can make the care job more challenging. The aide-client connection was affected by communication style, family and HC agency support, allotted care time, and job task boundaries. Interventions that address the safety of both clients and aides can influence HC job satisfaction and retention.